Computational exploration of biomedical HfNbTaTiZr and Hf0.5Nb0.5Ta0.5Ti1.5Zr refractory high-entropy alloys. (30th September 2021) - Bhandari, Uttam; Ghadimi, Hamed; Zhang, Congyan; Gao, Feng; Yang, Shizhong; Guo, Shengmin
Abstract: Refractory high entropy alloys (RHEAs) have been proven to be a potential candidate in the biomedical field due to their balanced mechanical properties and biocompatible composition. Recent experimental findings show that RHEAs like HfNbTaTiZr and Hf0.5 Nb0.5 Ta0.5 Ti1.5 Zr have good mechanical properties such as high polarization and wear resistance than others which establish them as potential materials for biomedical application. In this work, we performed first-principles density functional theory calculations on the mechanical and thermal properties of HfNbTaTiZr and Hf0.5 Nb0.5 Ta0.5 Ti1.5 Zr. The predicted lattice constant, density, Young's modulus, and Vickers hardness are consistent with the available experimental report, which verifies the accuracy of the applied model. The thermal coefficient of linear expansion of both RHEAs has been investigated by utilizing the Debye theory. The present methods could be applied to study other future RHEAs on exploration of their physical properties.